Pengaruh Konsep Tri Kaya Parisudha, Keefektifan Pengendalian Internal, Persepsi Kesesuaian Kompensasi Dan Implementasi Good Corporate Governance Terhadap Kecenderungan Kecurangan (Fraud) Pada Lembaga Perkreditan Desa Di Kabupaten Karangasem - Dewi A., Putu Novi Anesya; Atmadja, Anantawikrama Tungga (Universitas Pendidikan Ganesha, 2021)
This research aimed to determine the influence of the concept of tri kaya parisudha, the effectiveness of internal control, the perceptions of suitability of compensation, and the implementation of good corporate governance on the tendency of fraud in village credit institutions in Karangasem district. The populations in this study were all employees of village credit institutions in Karangasem district as many as 824 employees with the number of samples involved 89 respondents. The sampling method in this study was used a simple random sampling method. The data were collected by distributing questionnaires to employees who were the research samples. The data were analyzed by using the multiple linear regression analysis techniques with SPSS 25.0 for the windows program.The results show that (1) the concept of tri kaya parisudha has a negative and significant effect on the tendency of fraud, (2) the effectiveness of internal control has a negative and significant effect on the tendency of fraud, (3) the perceptions of the suitability of compensation has a negative and significant effect on the tendency of fraud, (4) the implementation of good corporate governance has a negative and significant effect on the tendency of fraud.